Working for Policy. - Colebatch, H. K. (Hal K.) (Amsterdam University Press, 2010)
There are now many people involved in 'making policy', but there is not a great deal written about how they do it. Most of the books on policy tend to refer obliquely, if at all, to the actual practice of policy work, and offer little guidance to policy workers or students of policy. 'Policy work' seems to be something that you learn on the job. This book addresses directly the nature of policy work.